Role of Nrf2 in Parkinson’s Disease: Toward New Perspectives - Yang, Xin-xing; Yang, Rong; Zhang, Feng (Frontiers in Pharmacology, 2022)
Parkinson's disease (PD) is one of the most common and chronic degenerative diseases in the central nervous system. The main pathology is the degenerative loss of dopaminergic neurons in the substantia nigra. However, the pathogenesis of PD is not caused by an independent factor. The diversity of these independent factors of PD, such as iron accumulation, oxidative stress, neuroinflammation, mitochondrial dysfunction, age, environment and heredity, makes the research progress of PD slow. Nrf2 has been well-known to be closely associated with the pathogenesis of PD and could regulate these induced factors development. Nrf2 activation could protect dopaminergic neurons and slow down the progression of PD. This review summarized the role of Nrf2 pathway on the pathogenesis of PD. Regulation of Nrf2 pathway might be one of the promising strategies to prevent and treat PD.